PENGARUH MULTI-FEEDSTOCK BIODIESEL (MINYAK KELAPA SAWIT, MINYAK ZAITUN, MINYAK CANOLA) TERHADAP UNJUK KERJA FOUR STROKE DIESEL ENGINE - Julian Wahyu Perdana; Edi Haryono; Eky Novianarenti (Proceedings Conference on Marine Engineering and its Application, 2023)
Biodiesel is a renewable fuel and is generally made from biological sources (vegetable and animal)and is environmentally friendly. Raw materials that can be used as biodiesel are palm oil, olive oil, andcanola oil. In this research, the mixing of the three raw materials into a composition (multi-feedstockbiodiesel) was carried out through the process of mixing biodiesel with HSD to produce B20, B35 andB100 fuel. This fuel will be tested on a four stroke diesel engine with a 1000 watt light load, as well asdata collection with variations of 900 rpm, 950 rpm, 1000 rpm and 1050 so that the most optimal testresults for power and torque are obtained, namely B100 while for gsfc test results the most optimal fuelis obtained, namely B35.